Optical and structural properties of Er-doped GaN/InGaN materials and devices synthesized by metal organic chemical vapor deposition - Ugolini, Cristofer Russell (Kansas State University, 2008)
The optical and structural properties of Er-doped GaN/InGaN materials and devices synthesized by metal organic chemical vapor deposition (MOCVD) were investigated. Er-doped GaN via MOCVD emits a strong photoluminescence (PL) emission at 1.54 um using both above and below-bandgap excitation. In contrast to other growth methods, MOCVD-grown Er-doped GaN epilayers exhibit virtually no visible emission lines. A small thermal quenching effect, with only a 20% decrease in the integrated intensity of the 1.54 um PL emission, occurred between 10 and 300 K. The dominant bandedge emission of Er-doped GaN at 3.23 eV was observed at room temperature, which is red-shifted by 0.19 eV from the bandedge emission of undoped GaN. An activation energy of 191 meV was obtained from the thermal quenching of the integrated intensity of the 1.54 um emission line. It was observed that surface morphology and 1.54 um PL emission intensity was strongly dependent upon the Er/NH3 flow rate ratio and the growth temperature. XRD measurements showed that the crystalline ordering of the (002) plane was relatively unperturbed for the changing growth environment. Least-squares fitting of 1.54 um PL measurements from Er-doped GaN of different growth temperatures was utilized to determine a formation energy of 1.82 ± 0.1 eV for the Er-emitting centers. The crystalline quality and surface morphology of Er-doped InGaN (5% In fraction) was nearly identical to that of Er-doped GaN, yet the PL intensity of the 1.54 um emission from Er-doped InGaN (5% In fraction) was 16 x smaller than that of Er-doped GaN. The drop in PL intensity is attributed to the much lower growth temperature in conjunction with the high formation energy of the Er- emitting centers. Er-doped InGaN grown at fixed growth temperature with different growth pressures, NH3 flow rates, and Ga flow rates was also investigated, and showed that increased In fractions also resulted in a smaller 1.54 um PL intensity. Er-doped InGaN p-i-n diodes were synthesized and tested. The electroluminescence (EL) spectra under forward bias shows strong Er based emission in the infrared and visible region. The different emission lines from EL spectra in contrast to PL spectra implies different excitation methods for the Er based emission in the p-i-n diode than in the PL excited epilayer.
Keywords: Metal organic chemical vapor deposition; Erbium; Gallium Nitride; Optical properties; Structural properties; Telecommunication; Engineering, Materials Science (0794); Physics, Condensed Matter (0611)